Human Papillomavirus High-risk Type Infection on Perianal Giant Condyloma Acuminatum - Rio Maruli Tampubolon; M. Izazi Hari Purwoko; Mutia Devi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Giant condyloma acuminatum (GCA) is a large form of condyloma acuminatum that become locally invasive, destructive, but non-metastasizing, caused by human papillomavirus (HPV). Giant condyloma is a rare disease, with only 0.1% incidence in the general population. Most commonly caused by HPV type 6 and 11 infections, in this case, reported HPV high-risk type. Case presentation: A 20-years-old man, the main complaint is enlarging, easy bleeding perianal tumor with pruritus and constipation for 2 months. Physical examination found skin-colored, verrucous surface. Some have smooth surface, cauliflower-like tumor on perianal region, size 7x4x2cm. Syphilis and HIV Serology laboratory tests are non-reactive. Koilocytes appear on histopathologic examination. High-risk HPV type detected on HPV genotyping. This patient was diagnosed as GCA. Topical agent 25% podophyllin tincture applied to the lesions once a week. Improvement appears after eighth-time therapy. Discussion: High-risk type HPV infection, detected in the patient, have an important role in GCA development. Decreased immune system and other risk factors also have a role in GCA.